3y-9+y+47=6y+40-4y

Simple and best practice solution for 3y-9+y+47=6y+40-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y-9+y+47=6y+40-4y equation:


Simplifying
3y + -9 + y + 47 = 6y + 40 + -4y

Reorder the terms:
-9 + 47 + 3y + y = 6y + 40 + -4y

Combine like terms: -9 + 47 = 38
38 + 3y + y = 6y + 40 + -4y

Combine like terms: 3y + y = 4y
38 + 4y = 6y + 40 + -4y

Reorder the terms:
38 + 4y = 40 + 6y + -4y

Combine like terms: 6y + -4y = 2y
38 + 4y = 40 + 2y

Solving
38 + 4y = 40 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
38 + 4y + -2y = 40 + 2y + -2y

Combine like terms: 4y + -2y = 2y
38 + 2y = 40 + 2y + -2y

Combine like terms: 2y + -2y = 0
38 + 2y = 40 + 0
38 + 2y = 40

Add '-38' to each side of the equation.
38 + -38 + 2y = 40 + -38

Combine like terms: 38 + -38 = 0
0 + 2y = 40 + -38
2y = 40 + -38

Combine like terms: 40 + -38 = 2
2y = 2

Divide each side by '2'.
y = 1

Simplifying
y = 1

See similar equations:

| -13-x=x-5 | | -4(3p+2)-46=3(4p+6) | | -2x-9=6x+15 | | 3.1(6.7+4.7n)=38.304+6.6n | | p^2+8p=0 | | 5(c-3)+9=3+c-9 | | 20+4x=8(x+6) | | 8x+3=6x+7 | | 3-6x=-(1-3x)+4 | | 8(x+4)+6=38 | | -24+3k=k-2k | | (4x^2)+16x+13=0 | | 13.7v-6.5=-2.3+8.3 | | n^2=-5n | | 2(x+4)-5x+7= | | 0=-6(y+2) | | 5=4(x-2)+9 | | 7+6x=-4(x-5)+7 | | 12-1.2(x-5)=22-2(x-4) | | -4(t+6)=4 | | -3-8x+5x=4-4x | | n^2+6n=-5 | | 3k+8k=8k-9 | | 5(x-7)+2=-28 | | 3x+5=3(x-9) | | -5(z+7)=-6z | | x*2-x=12 | | 5n-4(n-6)=2+2n | | 10-(3y-3)=2-4y | | x/8-1=-5 | | 2x*2-x=45 | | 3xy^2-2xy+2=-3y^2+y+4x |

Equations solver categories